Navigating Pedagogical Challenges: Student-Teacher Experiences in the Amaliyah Tadris Program at Islamic Boarding Schools Learning Interests - Fatimah, Putriana Ayu; Saadillah (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study explores the real-life challenges faced by final-year high school students participating in the Amaliyah Tadris program at an Islamic boarding school, particularly when teaching English. Using a qualitative narrative inquiry approach, the researcher interviewed eight student-teachers from Darul Hijrah Islamic Boarding School for Female. These in-depth interviews captured their teaching experiences, the difficulties they encountered, and the strategies they used to overcome them. The findings reveal that many student-teachers struggled with nervousness, limited teaching experience, classroom management issues, and time constraints in preparing I’dad (Preparation Book). In addition, they faced external obstacles such as unmotivated students, poor classroom conditions, and difficulties in helping students with pronunciation and vocabulary. Despite these challenges, the participants demonstrated resilience by preparing independently, using visual aids and engaging activities, adapting their communication styles, and seeking support from mentor teachers. This research highlights the need for stronger guidance, better training, and emotional readiness for student-teachers before entering real classrooms. It also offers practical insights for improving teacher preparation programs, especially within Islamic boarding schools. The study emphasizes the importance of supporting young educators not only pedagogically, but also emotionally and psychologically, to help them grow into confident and capable future teachers.